2010
DOI: 10.1111/j.1420-9101.2009.01911.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear selection and the evolution of variances and covariances for continuous characters in an anole

Abstract: The pattern of genetic variances and covariances among characters, summarized in the additive genetic variance‐covariance matrix, G, determines how a population will respond to linear natural selection. However, G itself also evolves in response to selection. In particular, we expect that, over time, G will evolve correspondence with the pattern of multivariate nonlinear natural selection. In this study, we substitute the phenotypic variance‐covariance matrix (P) for G to determine if the pattern of multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 87 publications
2
19
0
Order By: Relevance
“…These trait combinations corresponded to alternative broad and narrow perch diameters, respectively, and are consistent with the well‐studied limb length‐perch diameter relationship in A. sagrei . Additionally, Revell et al (2010) found some support for the congruence of nonlinear selection and P in the trunk‐ground anole, A. cristatellus , suggesting natural selection may have influenced the evolution of genetic architecture in this species. Unfortunately, most individual selection coefficients obtained by Revell et al were not significantly different from zero, precluding an explicit analysis of “selective lines of least resistance” with a well‐estimated adaptive landscape for divergence patterns in this study (Arnold et al 2008; Hohenlohe and Arnold 2008).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These trait combinations corresponded to alternative broad and narrow perch diameters, respectively, and are consistent with the well‐studied limb length‐perch diameter relationship in A. sagrei . Additionally, Revell et al (2010) found some support for the congruence of nonlinear selection and P in the trunk‐ground anole, A. cristatellus , suggesting natural selection may have influenced the evolution of genetic architecture in this species. Unfortunately, most individual selection coefficients obtained by Revell et al were not significantly different from zero, precluding an explicit analysis of “selective lines of least resistance” with a well‐estimated adaptive landscape for divergence patterns in this study (Arnold et al 2008; Hohenlohe and Arnold 2008).…”
Section: Discussionmentioning
confidence: 93%
“…Several recent studies have measured selection in Anolis lizard populations (Losos et al 2004, 2006; Thorpe et al 2005; Calsbeek and Irschick 2007; Calsbeek and Smith 2007, 2008; Revell et al 2010), demonstrating its feasibility and suggesting measures of the multivariate adaptive landscape could be incorporated explicitly into analyses of phenotypic evolution in this system. Most studies have focused on the relationship between variation in morphological traits (e.g., body size, limb length) and survival using the truck‐ground species A. sagrei .…”
Section: Discussionmentioning
confidence: 99%
“…Maximum-likelihood reconstructions were also done in Mesquite to take advantage of the branch-length data incorporated in the tree (see Schluter et al 1997;Pagel 1999;Lewis 2001;Revell et al 2010).…”
Section: Methodsmentioning
confidence: 99%
“…That is, the predictions of models emphasizing “genetic constraint” and “selection” are not mutually exclusive. Although separate lines of empirical study offer some support for intraspecific covariances (Brodie, ; Hunt, Blows, Zajitschek, Jennions, & Brooks, ; Revell et al., ; also see Roff & Fairbairn, ) or among‐species covariances (Hohenlohe & Arnold, ) corresponding with the pattern of nonlinear selection, we are not aware of an empirical study that has evaluated the concordance of among all three sets of parameters; that is, whether γ can simultaneously predict patterns of covariance observed at both micro‐ and macroevolutionary scales. In this study, we employed a genus of true bug ( Phymata , Order: Reduviidae) to test the conjecture that patterns of both standing trait variation (in one species) and divergence among related taxa are explained by strong nonlinear sexual selection.…”
Section: Introductionmentioning
confidence: 99%